2020
DOI: 10.3390/ijms21114039
|View full text |Cite
|
Sign up to set email alerts
|

Elastography Techniques for the Assessment of Liver Fibrosis in Non-Alcoholic Fatty Liver Disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) is expected to increase in prevalence because of the ongoing epidemics of obesity and diabetes, and it has become a major cause of chronic liver disease worldwide. Liver fibrosis is associated with long-term outcomes in patients with NAFLD. Liver biopsy is recommended as the gold standard method for the staging of liver fibrosis. However, it has several problems. Therefore, simple and noninvasive methods for the diagnosis and staging of liver fibrosis are urgently need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 88 publications
0
37
1
1
Order By: Relevance
“…Various non-invasive diagnostic methods have been developed based on the assessment of liver stiffness measurement (LSM), which is a promising surrogate biomarker of liver fibrosis stage [ 37 ]. Among the elastography techniques available, magnetic resonance elastography (MRE), a magnetic resonance imaging (MRI)-based technique, has shown promising results [ 8 , 39 ]. However, MRE has several disadvantages which have limited its use in clinical practice and in people with obesity.…”
Section: Assessment Of Liver Fibrosis In Nafldmentioning
confidence: 99%
See 1 more Smart Citation
“…Various non-invasive diagnostic methods have been developed based on the assessment of liver stiffness measurement (LSM), which is a promising surrogate biomarker of liver fibrosis stage [ 37 ]. Among the elastography techniques available, magnetic resonance elastography (MRE), a magnetic resonance imaging (MRI)-based technique, has shown promising results [ 8 , 39 ]. However, MRE has several disadvantages which have limited its use in clinical practice and in people with obesity.…”
Section: Assessment Of Liver Fibrosis In Nafldmentioning
confidence: 99%
“…Non-alcoholic fatty liver disease (NAFLD) has become the most common liver disease and the leading cause of chronic liver disease worldwide [ 8 , 9 ]. NAFLD is strongly linked to obesity [ 10 , 11 , 12 ], with a reported prevalence of approximately 80% in people with obesity and only 16% in people with a normal BMI and no known metabolic risk factors [ 10 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yajima et al have shown that the combination of ultrasonographical findings of liver–kidney contrast, vascular blurring, and deep attenuation enables us to grade fatty change semi-quantitatively [ 8 ]. Magnetic resonance elastography (MRE) and ultrasound elastography have been reported as effective methods to compensate for these problems [ 11 , 12 ]. MRE has a higher area under the receiver operating characteristic curve (AUROC) value than one type of ultrasound elastography, FibroScan (Echosens, Paris, France) [ 12 , 13 ], but it is costly to implement.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance elastography (MRE) and ultrasound elastography have been reported as effective methods to compensate for these problems [ 11 , 12 ]. MRE has a higher area under the receiver operating characteristic curve (AUROC) value than one type of ultrasound elastography, FibroScan (Echosens, Paris, France) [ 12 , 13 ], but it is costly to implement. FibroScan is an evidence-based, transient elastography instrument for non-invasive evaluation of liver steatosis and fibrosis [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has shown good accuracy in MAFLD, particularly for advanced fibrosis and cirrhosis detection (6), and has been introduced into the practical guidelines for MAFLD diagnosis and management (7). However, TE has several limitations including imperfect prediction (8). Therefore, combinations of TE with other markers have been explored, for instance, a recent multi-center study developed and validated a score consisting of TE, controlled attenuation parameter (CAP) and aspartate aminotransferase (AST) to identify MAFLD patients with inflammatory activity, steatohepatitis and significant fibrosis (9).…”
Section: Introductionmentioning
confidence: 99%